Apexification of immature teeth with calcium oxide: Three case reports [2] - Bodrumlu E.; Cicek E.; Guler B. (Nova Science Publishers, Inc., 2015)
Calcium oxide, available for decades as a root canal filling material, has not been frequently used in recent years due to its lack of radiopacity, and due to the expectation that it would lead to an excess of root fractures. These case reports were performed to determine the clinic and radiographic success of calcium oxide in the apexification treatment. This clinical report describes an apexification procedure on three maxillary central incisors presenting with chronic apical periodontitis. The pulp of the teeth had become necrotic following a traumatic injury. According to the treatment procedure the root canals were biomechanically prepared, medicated and filled with calcium oxide to stimulate hard tissue barrier formation. Follow-up clinical and radiographic examinations confirmed apical barrier at 6 months. It is concluded that calcium oxide may be considered a safe and viable alternative to other current methods of apexification. © 2015 Nova Science Publishers, Inc.
Keywords: Apexification; Calcium oxide; Root canal treatment